Dynamical anisotropic magnetoelectric effects at ferroelectric/ferromagnetic insulator interfaces *Project supported by the National Natural Science Foundation of China (Grant Nos. 11474138 and 11834005), the Fund from the Ministry of Science and Technology of China (Grant No. CN-SK-8-4), the Science Foundation from the Slovak Academy of Sciences (Grant No. 2/0059/17), and the Science Fund from the Slovak Research and Development Agency (Grant No. APVV SK-CN-2017-0004). (September 2019) - Li 李, Yaojin 耀进; Koval, Vladimir; Jia 贾, Chenglong 成龙
Abstract : The interfacial magnetoelectric interaction originating from multi-orbital hopping processes with ferroelectric-associated vector potential is theoretically investigated for complex-oxide composite structures. Large mismatch in the electrical permittivity of the ferroelectric and ferromagnetic materials gives rise to giant anisotropic magnetoelectric effects at their interface. Our study reveals a strong linear dynamic magnetoelectric coupling which genuinely results in electric control of magnetic susceptibility. The constitutive conditions for negative refractive index of multiferroic composites are determined by the analysis of light propagation.